2016
DOI: 10.1101/079467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociable Roles of Ventromedial Prefrontal Cortex and Anterior Cingulate in Subjective Valuation of Prospective Effort

Abstract: The perceived effort level of an action shapes everyday decisions. Despite the importance of these perceptions for decision-making, the behavioral and neural representations of the subjective cost of effort are not well understood. While a number of studies have implicated anterior cingulate cortex (ACC) in decisions about effort/reward trade-offs, none have experimentally isolated effort valuation from reward and choice difficulty, a function that is commonly ascribed to this region. We used functional magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Another situation that requires cognitive control is difficult decision-making when two simultaneously presented options have similar net value (Chong et al, 2017;Hunt et al, 2012;Klein-Flugge et al, 2016;Massar et al, 2015;Shenhav et al, 2013). Indeed, studies that have independently manipulated net value and decision difficulty showed that these frontal regions, particularly the dorsal ACC, specifically tracked decision difficulty (Hogan et al, 2017;Westbrook et al, 2019) while, in contrast, the vmPFC uniquely tracked net value (Westbrook et al, 2019). Taken together, these findings suggest that this distinct frontal network is recruited more specifically for cognitive control, such as response planning and option comparison, and that effortrelated value integration is still processed in the core valuation network (e.g., vmPFC and VS) that have been identified in other cost domains.…”
Section: Introductionmentioning
confidence: 99%
“…Another situation that requires cognitive control is difficult decision-making when two simultaneously presented options have similar net value (Chong et al, 2017;Hunt et al, 2012;Klein-Flugge et al, 2016;Massar et al, 2015;Shenhav et al, 2013). Indeed, studies that have independently manipulated net value and decision difficulty showed that these frontal regions, particularly the dorsal ACC, specifically tracked decision difficulty (Hogan et al, 2017;Westbrook et al, 2019) while, in contrast, the vmPFC uniquely tracked net value (Westbrook et al, 2019). Taken together, these findings suggest that this distinct frontal network is recruited more specifically for cognitive control, such as response planning and option comparison, and that effortrelated value integration is still processed in the core valuation network (e.g., vmPFC and VS) that have been identified in other cost domains.…”
Section: Introductionmentioning
confidence: 99%